2020
DOI: 10.1080/17482631.2020.1815487
|View full text |Cite
|
Sign up to set email alerts
|

Becoming a nomad when hospitalized with a neurological disease: a phenomenological study

Abstract: Patients with a neurological disease are affected by their ability to maintain focus and are easily disturbed by outside stimuli. Few studies have investigated how sensory impressions from the physical environment contribute to patient's wellbeing during hospitalization. However, no studies have explored the meaning of the environment to patients with a neurological disease during hospitalization. To understand what it is like to be a patient in a hospitalized environment at the neurological department. Nine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Thus, the aesthetic places became concrete places in which the participants could distance themselves from fellow patients and avoid the inciting noise. In our recent study (Beck et al, 2020 ) we showed how hospitalized patients with neurological symptoms become nomads during hospitalization in order to find places to endure being present in the hospital environment. (Beck et al, 2020 ) paved the way for this recent study, in which we conducted an aesthetic experiment in clinical practice.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, the aesthetic places became concrete places in which the participants could distance themselves from fellow patients and avoid the inciting noise. In our recent study (Beck et al, 2020 ) we showed how hospitalized patients with neurological symptoms become nomads during hospitalization in order to find places to endure being present in the hospital environment. (Beck et al, 2020 ) paved the way for this recent study, in which we conducted an aesthetic experiment in clinical practice.…”
Section: Resultsmentioning
confidence: 99%
“…Characteristics of most neurological diseases is that it challenges humans on its senses. It is also evident that hospitalization to the neurological unit has existential impact on people, hence, patients can experience loneliness during their stay at the hospital (Beck, et al, 2016 , 2018 , 2019 , 2020 ). Recent studies have shown how patients are becoming nomads lurking around to find breathing spaces when they were not offered a calm and familiar environment (Beck et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations